(untitled) (International Journal of Environmental Sciences, 2025)
Climate change primarily has three troubling aspects; dispersion of cause and effect, inadequacy of the institution and fragmentation of agency, owing to its polycentric nature. It is one of the greatest issues for mankind not because food security, energy security, poverty, and hunger among others are less important, but because climate change has the capability to aggravate these already existing crises in the world. Hence, the infusion of distributive justice and capabilities approach in the emerging idea of climate justice, has immense potential to mitigate the adverse impact of climate change, mainly on the vulnerable section of the society and help in the making of an ecological citizenship. Distributive justice with respect to climate change is to make sure that everyone can derive the benefits of a reliable source of energy. On the other hand, the introduction of the capabilities approach shall bridge the gap between the idealistic attributes of climate justice with the reality of policymaking. The present paper shall engage with the idea of the fulfilment of environmental needs through the lens of Maslow’s Hierarchy of Needs and how these needs can be satisfied through the notion of distributive justice and capabilities approach which will ultimately help in making an ecological citizenship and securing climate justice by actually bridging the gap between the mitigation and adaptation policies of climate change and its efficient implementation. Talking particularly in the Indian context, this shall help India in the fulfilment of its INDC targets under the Paris Agreement which requires them to be based on the “highest possible ambition with progression in each subsequent target.”.